New early Pleistocene hominin teeth from the Swartkrans Formation, South Africa. Issue 100 (November 2016) - Pickering, Travis Rayne; Heaton, Jason L.; Sutton, Morris B.; Clarke, Ron J.; Kuman, Kathleen; Senjem, Jess Hutton; Brain, C.K.
Abstract: We describe 14 hominin teeth and tooth fragments excavated recently from Swartkrans Cave (South Africa). The fossils derive from Members 1 (Lower Bank) and 3, from the Member 2/3 interface and from two deposits not yet assigned to member (the "Talus Cone Deposit" and the "Underground North Excavation" [UNE]) of the Swartkrans Formation, and include the first hominin fossil from the UNE, the two smallest Paranthropus robustus deciduous maxillary second molars in the entire hominin fossil record, and one of the smallest P. robustus permanent maxillary second molars from Swartkrans. The small permanent molar is accompanied by another tooth from a different individual but from the same stratigraphic level of the Swartkrans Formation; this second tooth is among, if not, the largest P. robustus permanent maxillary first molars known from anywhere—lending credence to assertions that degrees of body size sexual dimorphism previously ascribed to this species may be underestimated. It is more equivocal whether this evidence also supports hypotheses proposing that P. robustus assemblages from Swartkrans (as well as those from other South African cave sites) formed through the taphonomically biasing actions of large carnivores.